RANCANG BANGUN SISTEM INFORMASI PEMBAYARAN SUMBANGAN PEMBINAAN PENDIDIKAN (SPP) PADA SMAK ST. GREGORIUS SUMBAWA MENGGUNAKAN METODE WATERFALL - Ertina Melfiani; Titi Andriani; Muhammad Hidayatullah (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2020)
St. Gregorius Senior High School is one of the schools in Sumbawa which was founded by Yayasan Insan Mandiri. Administration data processing process at St. Gregorius Senior High School Sumbawa uses Microsoft Excel so that optimization of information technology is one solution to improve the performance of administrative staff so that work becomes more efficient. Therefore, the system that is needed one of them is with a web-based information system. The information system in this study was designed using PHP CodeIgniter framework and MySQL database. The system development method used is the waterfall method. The results of this study are the Information System for the Payment of Educational Development Donations (SPP) at the St. Gregorius Senior High School Sumbawa who is able to process administrative data on SPP payments more efficiently. In the future, this information system can be developed using existing features into a complex system and capable of developing technology.